2000
DOI: 10.3354/meps194219
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the growth dynamics of Antarctic krill Euphausia superba

Abstract: A time-dependent, size-structured, bioenergetically based model was developed to examine the growth dynamics of Antarctic krill Euphausia superba 2 to 60 mm in size. The metabolic processes included in the model are ingestion, a baseline respiration, respiratory losses due to feeding and digestion, and an activity-based respiration factor. The total of these processes, net production, was used as the basis for determining the growth or shrinkage of individuals. Size-dependent parameterizations for the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 23 publications
(34 reference statements)
4
102
1
Order By: Relevance
“…For 40 mm krill, this swimming speed is similar to the average speed (30 cm s -1 ) of currents at the Southern ACC Front (Orsi et al 1995). Modeling studies (Hofmann et al 1998, Hofmann & Lascara 2000 suggest that krill with initial sizes of 2 mm and 10 mm can develop to 10-12 mm and 20-30 mm, respectively, in 140 to 160 d.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…For 40 mm krill, this swimming speed is similar to the average speed (30 cm s -1 ) of currents at the Southern ACC Front (Orsi et al 1995). Modeling studies (Hofmann et al 1998, Hofmann & Lascara 2000 suggest that krill with initial sizes of 2 mm and 10 mm can develop to 10-12 mm and 20-30 mm, respectively, in 140 to 160 d.…”
Section: Introductionmentioning
confidence: 59%
“…Simulations of Antarctic krill growth and development are obtained using the model described in Hofmann & Lascara (2000). This size-structured, physiologically based model gives the time-dependent (t) change in the number of krill individuals (N ) in a given size class, j, as:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Murphy & Reid (2001) reproduced monthly changes in the size distribution of krill at South Georgia using a model that incorporated seasonal variability in natural mortality and growth rate. Also, Hofmann & Lascara (2000) found that it was necessary to include a seasonal change in respiration rates in order for their bioenergetic model to replicate observed patterns of growth and shrinkage.…”
Section: (1) General Characteristicsmentioning
confidence: 99%